2002
DOI: 10.1111/j.1365-2621.2002.tb10626.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xylanase and Peroxidase on Soluble and Insoluble Arabinoxylans in Wheat Bread Dough

Abstract: Bread doughs supplemented with xylanase and xylanase plus peroxidase were fractionated into 4 insoluble and 3 soluble fractions. Chemical analysis and high-performance size-exclusion chromatography analysis of apparent molecular weight distribution indicated that xylanase acts on both cold-water-extractable arabinoxylans and on those that can be solubilized from cell wall fragments by hot water extraction. Peroxidase action increased the amount of insoluble small cell wall fragments, notably the amount of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
(12 reference statements)
0
14
0
1
Order By: Relevance
“…The micrographs of chapatis prepared from xylanase treated dough showed starch granules with slight distortion and rupturing with ellipsoidal shape and were embedded in the gluten protein (Fig.3eD). Xylanase solubilizes the insoluble pentosans, leading to a change in water distribution (Hilhorst et al, 2002;Martin & Anaya, 2003). Prabhasankar et al (2004) reported that microstructure of parottas treated with xylanase showed slight distortion Means of the same column followed by different letters are significantly different (p < 0.05).…”
Section: Influence Of Enzymes On Microstructure Of Chapatismentioning
confidence: 99%
“…The micrographs of chapatis prepared from xylanase treated dough showed starch granules with slight distortion and rupturing with ellipsoidal shape and were embedded in the gluten protein (Fig.3eD). Xylanase solubilizes the insoluble pentosans, leading to a change in water distribution (Hilhorst et al, 2002;Martin & Anaya, 2003). Prabhasankar et al (2004) reported that microstructure of parottas treated with xylanase showed slight distortion Means of the same column followed by different letters are significantly different (p < 0.05).…”
Section: Influence Of Enzymes On Microstructure Of Chapatismentioning
confidence: 99%
“…The xylanases isolated to date from Thermotoga species are all proved to be extremely thermostable, and represent an attractive source of catalyst for the biotechnology industries (Bergquist et al, 2001). While many researchers have investigated the effects of the mesophilic xylanases on breadmaking; comparatively little has been done on the thermostable xylanases (Courtin & Delcour, 2002;Hilhorst et al, 2002;Laurikainen, Härkö nen, Autio, & Poutanen, 1998;Maat et al, 1992;McCleary, 1986;Norma & Guillermo, 2003). Until the present study, the thermostable xylanases have not been investigated in baking.…”
Section: Introductionmentioning
confidence: 96%
“…2 -7 SBP with a pI of 4.1 and an apparent molecular mass of 37 kDa is a glycoprotein from soybean hulls. 3 Peroxidases have been used in the bread-baking industry, 8,9 are cross-linking agents for proteins 10 and are oxidative coupling agents for producing phenolic resins. 11 BBI is a serine protease inhibitor which, when isolated and purified from soybean cotyledon, possesses a pI of 4.2, 12 has 71 amino acid residues and a molecular mass of 7850 Da and simultaneously inhibits both trypsin and chymotrypsin.…”
Section: Introductionmentioning
confidence: 99%